ANALISIS MANAJEMEN RISIKO PEMBIAYAAN PRODUK CICIL EMAS PADA BANK SYARIAH MANDIRI KANTOR CABANG PEMBANTU BOGOR JALAN BARU - Anisa Rahman; Rully Trihantana; Ria Kusumaningrum (SAHID BANKING JOURNAL, 2022)
concerning Implementation of Risk Management for Islamic Commercial Banks (BUS) and Sharia Business Units (UUS), and the solutions provided to the risks that occur at BSM KCP Bogor Jalan Baru. This study uses a qualitative approach, with the type of qualitative descriptive research. The data used in this study were obtained from observations at the research site, direct interviews with relevant sources at BSM KCP Bogor Jalan Baru. The results of this research show: First, the application of risk management for gold installment financing products at BSM KCP Bogor Jalan Baru is carried out in 4 stages, namely: identification, measurement, monitoring, and risk control. Second, the implementation of risk management carried out by BSM KCP Bogor Jalan Baru is in accordance with POJK Number 65/POJK.03/2016. Third, the highest risk that occurs in gold installment financing products is credit or financing risk, so the solution is that banks must pay more attention to the risk identification stage, especially analysis on the 5C aspect.